INFLUENCE OF SUBCLINICAL KETOSIS IN COWS ON FORMATION OF COLOSTRAL IMMUNITY IN CALVES - S. V. Vasilieva (SPb RAACI, 2021)
The health of the newborn depends entirely on the state of the mother’s body throughout the pregnancy. Ensuring optimal conditions for keeping pregnant animals is based, first of all, on adequate feeding and ensuring the sanitary and hygienic conditions of the environment. The cow’s body undergoes a great load during the transition period, which begins 3 weeks before calving and lasts for six weeks. When the technology of feeding and housing is violated, during this period, metabolic disorders often occur in cows, which are manifested by increased production of ketones. It is known that the development of immunity in the early postnatal period in a calf largely depends on the timely feeding of colostrum. Maternal immunoglobulins from colostrum enter the systemic circulation of the newborn in the small intestine through the tubular system of epithelial cells by pinocytosis.The aim of the study is to study the effect of subclinical ketosis in mothers cows on the formation of colostral immunity in calves born from them.For the study, pregnant cows 3-6 years old were selected 3-7 days before delivery. Urine and blood samples were taken from the cows. In order to identify subclinical ketosis in cows, urine was tested for ketones. According to the results of the study, two groups of 10 animals were formed – in the first group (experimental) the level of ketone bodies in the urine ranged from 1.8 to 3.7 mmol/l, in the second group (control) ketones were not found in the urine. Immediately after calving, portions of colostrum were taken from the cows, and blood was taken from newborn calves a day after the first colostrum was fed. The content of immunoglobulins was studied in skim colostrum and in the blood serum of newborn calves. In the blood serum of day-old calves, the content of total protein was also determined by the biuret method, albumin – by the photometric method with bromcresol green.According to the results of the study, a decrease in the classes of immunoglobulins G, M and A was found in the blood serum of cows before calving by 19.1-23.5%, in colostrum – by 23.7-34.4%, and in the blood serum of day old calves – by 21.7-27.6%. The decrease in IgM concentration was determined to the greatest extent. Subclinical ketosis of mothers had practically no effect on the content of albumin in the blood of calves.